2007
DOI: 10.1007/s10162-007-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes of Mechanics Measured in the Gerbil Cochlea

Abstract: This report describes stiffness and best frequency measurements obtained in vitro from the basilar membrane of the gerbil cochlea at the onset of hearing, during hearing maturation, and after hearing has matured. Our stiffness data constitute the first direct experimental evidence of developmental stiffness changes in the basal and middle turns. Stiffness changes by a factor of 5.5 in the basal turn between postnatal day 11 and adult, and the difference from adult is statistically significant for all ages meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Studies in several different mammalian species have demonstrated the presence of broad tuning curves at the time of hearing onset (Dolan et al, 1985;Echteler et al, 1989;Emadi and Richter, 2008;Overstreet and Ruggero, 2002;Romand, 1983;Walsh, 1986). Moreover, even before hearing onset, positionspecific changes in stereociliary bundle morphology become evident in both mammals and birds (Lelli et al, 2009;Tilney and Saunders, 1983).…”
Section: Development Of Tonotopic Specialization In the Auditory Sensmentioning
confidence: 95%
“…Studies in several different mammalian species have demonstrated the presence of broad tuning curves at the time of hearing onset (Dolan et al, 1985;Echteler et al, 1989;Emadi and Richter, 2008;Overstreet and Ruggero, 2002;Romand, 1983;Walsh, 1986). Moreover, even before hearing onset, positionspecific changes in stereociliary bundle morphology become evident in both mammals and birds (Lelli et al, 2009;Tilney and Saunders, 1983).…”
Section: Development Of Tonotopic Specialization In the Auditory Sensmentioning
confidence: 95%
“…While the initial rise in stiffness can be attributed to the coupling of the sensor to the tissue, it has been argued that the plateau reflects the relevant stiffness of the tissue. It has been assumed that the tissue can be approximated by a system of parallel and radially oriented beams and that the return force on the sensor results from the increasing number and stiffness of those beams (Emadi et al 2002;Emadi and Richter 2008;Emadi et al 2004;Gummer et al 1981;Miller 1985;Richter et al 2007;Vôldrich, 1978). In other words, the plateau stiffness has been suggested to reflect the stiffness of the embedded collagen fibers.…”
Section: Plateau Stiffnessmentioning
confidence: 99%
“…Our conclusion is that the second stiffness plateau of the measurements is substantially less, by a factor of 2-5, than the linear stiffness of the BM. This explains the long initial plateau spanning over 10-25 µm of deflection observed consistently in the measurements by Emadi et al [7,8] and Mountain et al [16,17], which they described as noise possibly because the behavior is contrary to the expectation of a monotonically increasing stiffness. In fact, Emadi et al [7] commented that the measured plateau stiffness may not be the physiologically relevant one, and that the relevant stiffness might occur at a much smaller deflection.…”
Section: Point-loading Resultsmentioning
confidence: 61%
“…This distribution of volume compliance is used for an "equivalent flat plate" to compute the 3D traveling waves for gerbil in [24]. The postnatal developmental increase in best frequency [8,15] can also be explained with Eq. (1) by the calculated decrease in compliance due to the increase in upper and lower band thicknesses [20].…”
Section: Pressure-loading Behaviormentioning
confidence: 99%